Hubungan Tingkat Pengetahuan Masyarakat Terhadap Kesediaan Diri Vaksinasi COVID-19 RW 01 Kecamatan Cineam - Anggriani, Ani; Sutrisno, Entris; Saskia, Puti Bela (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: The spread of the COVID-19 virus is rapidly expanding so that it becomes a big problem due to the increasing number of positive patient cases and cases of patients dying. Various efforts have been made, one of which is implementing a vaccination program with the aim of being able to work effectively by producing specific antibodies in the body so that it can reduce the incidence and break the chain of transmission. The attitude of the community towards their willingness to carry out the vaccination program still raises pros and cons. On November 4, 2021, it was recorded that Tasikmalaya Regency was ranked first as the region with the lowest vaccination rate in West Java. This study aims to analyze whether there is a significant relationship between the level of public knowledge on self- availability for the COVID-19 vaccine in the RW 01 area, Cineam District, Tasikmalaya Regency. This research is included in the type of quantitative research with analytical observational method with a cross sectional approach. Data were collected by distributing questionnaires and obtained a sample of 338 respondents. Data were analyzed using SPSS for frequency test and correlation test with Spearman Rank. The results obtained for the level of community knowledge of 88.9% and self-willingness of 67.8%, and the correlation test obtained is a significance value of 0.000 (0.000 <0.05) indicating a significant relationship between the level of knowledge and the presence of the community for implement a vaccination program.